2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347127
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional ballisto- and seismo-cardiography: HIJ wave amplitudes are poorly correlated to maximal systolic force vector

Abstract: Ballistocardiography was recorded in 3-D on a free floating astronaut in space as well as on healthy volunteers participating to the ESA 55(th) and DLR 19(th) parabolic flights campaigns. In this paper we demonstrate further the usefulness of recording and analyzing ballistocardiograms (BCG) in three dimensions. The spatial curves of the displacement, velocity and acceleration vectors are analyzed instead of their individual 2-D components. The maximum magnitude of the force vector is shown to be poorly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
(3 reference statements)
0
11
0
Order By: Relevance
“…The technical details of our procedure are similar to what we have done in previous studies and can be found with more details here [3,4,6].…”
Section: Methodsmentioning
confidence: 90%
“…The technical details of our procedure are similar to what we have done in previous studies and can be found with more details here [3,4,6].…”
Section: Methodsmentioning
confidence: 90%
“…Data were exported and processed offline using a specific toolbox written in Matlab version 9.5 R2018b (Mathworks ® ). Further details regarding this methodology have been published previously (Prisk et al 2001, Migeotte et al 2012, Migeotte et al 2016, Hossein et al 2019. P, Q, R, S, and T waves on the ECG were automatically identified and used as reference points for the identification of each cardiac cycle.…”
Section: Signal Processingmentioning
confidence: 99%
“…For each cardiac cycle, ECG, dICG and BCG signals were resampled to a normalized time axis [9], [12]. Shortly: the time axis corresponds to a normalization of the time between two consecutive heart beats from 0 to 1000.…”
Section: B Ensemble Averagementioning
confidence: 99%
“…In previous studies [3], [9], [10], [12], 3D-ballistocardiograms were obtained during a space mission and PF, in order to characterize the BCG signal in µG. The present study inscribes in the continuation of those studies, to further investigate the ballistocardiogram (BCG) in the µG environment, where no other forces than those of cardiac contractions are acting on the body.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation